Penerapan Media Sosial Dalam Kegiatan Penyuluhan Pertanian Di Jawa Tengah Sebuah Narrative Review - Larasati Puspita Saridewi (LP3M Universitas Putra Bangsa, 2024)
This research aims to determine the application of social media in agricultural extension activities in Central Java by analyzing research themes/topics, research methods and research results. The research method uses a qualitative approach with data processing using a literature review of three Garuda database indexed references with a publication range of 2016 - 2023. The research results show that research regarding the application of social media in agricultural extension activities in Central Java is quite good and can have a positive impact on accuracy, efficiency and effectiveness of extension and increasing agricultural productivity. The social media most often used for agricultural extension activities are WhatsApp, Facebook, YouTube and Instagram. There is a gap between needs and satisfaction in using WhatsApp to meet the needs of agricultural instructors, but the relationship between needs and satisfaction is very strong.